Impact of mtG3PDH inhibitors on proliferation and metabolism of androgen receptor-negative prostate cancer cells: Role of extracellular pyruvate. - Floriana Jessica Di Paola; Luiza Hd Cardoso; Efterpi Nikitopoulou; Bianca Kulik; Sandra Rühl; Alexander Eva; Natascha Sommer; Thomas Linn; Erich Gnaiger; Klaus Failing; Kathrin Büttner; Christian Frezza; et al. (PLoS ONE)
Mitochondrial glycerol 3-P dehydrogenase (mtG3PDH) plays a significant role in cellular bioenergetics by serving as a rate-limiting element in the glycerophosphate shuttle, which connects cytosolic glycolysis to mitochondrial oxidative metabolism. mtG3PDH was identified as an important site of electron leakage leading to ROS production to the mitochondrial matrix and intermembrane space. Our research focused on the role of two published mtG3PDH inhibitors (RH02211 and iGP-1) on the proliferation and metabolism of PC-3 and DU145 prostate cancer cells characterized by different mtG3PDH activities. Since pyruvate as a substrate of lactate dehydrogenase (LDH) may represent an escape mechanism for the recycling of cytosolic NAD+ via the glycerophosphate shuttle, we investigated the effect of pyruvate on the mode of action of the mtG3PDH inhibitors. Extracellular pyruvate weakened the growth-inhibitory effects of RH02211 and iGP-1 in PC-3 cells but not in DU145 cells, which correlated with higher H-type LDH and lower mitochondrial glutamate-oxaloacetate transaminase in DU145 cells. In the pyruvate-low medium, the strength of inhibition was more pronounced in PC-3 cells, characterized by higher mtG3PDH activities compared to DU145 cells. Pyruvate conversion rates (production in pyruvate-low and consumption in pyruvate-high PC-3 cells) were not impaired by RH02211 and iGP-1, suggesting that the conversion of extracellular pyruvate to lactate was not the primary factor responsible for the weakening effect of extracellular pyruvate on the RH02211-induced inhibition of PC-3 proliferation. In pyruvate-high PC-3 cells, the intracellular glycerol-3-P and dihydroxyacetone-P concentrations were consistent with an inhibition of mtG3PDH. In contrast, in pyruvate-low cells, the concentrations of these metabolites suggested an activation of mtG3PDH in parallel with an impairment of cytosolic G3PDH by RH02211. Of all metabolic characterizations recorded in this study (fluxes, intracellular intermediates, O2 consumption and H2O2 production), the decrease in glutaminolysis correlated best with the RH02211-induced inhibition of proliferation in pyruvate-low and pyruvate-high PC-3 cells.